Procedimento de observação de pareamento de estímulos e a emergência de nomeação completa em crianças com autismo - BRASIL, Michelle Abdon (Universidade Federal do Pará, 2020)
Full naming is a higher order behavioral relationship in which the individual responds to a class of objects and/or events by combining the listener and speaker functions without direct training. More recently, the Stimulus Pairing Observation Procedure (SPOP) has been shown to be an alternative to develop bidirectional naming in individuals who do not have such ability yet. The SPOP consists of successive presentations of pairs of stimuli where the only response required from the individual is the observation response. At the same time, no response emitted by the individual is differentially reinforced. The present study investigated the effect of SPOP on the induction of full naming in four children with autism spectrum disorder with limited verbal repertoire. It was also evaluated the effects of the presence or not of listener unidirectional naming in the eventual acquisition of full naming. The experiment used the multiple probe design across participants. The procedure was composed for 1. Assessment of words articulation, 2. Pretests for tact and object selection, 3. Listener unidirectional naming test, 4. Full naming probes, 5. Baseline and 6. SPOP with more pairings. Results demonstrated that in addition to being effective in establishing tact and listener responses, SPOP was effective in establishing full naming for one of the participants. The data also suggest that the induction of this behavior in this population can be facilitated by the previous presence of listener unidirectional naming in the verbal repertoire of the individuals.